THE OPSONIZATION TEST IN BRUCELLOSIS - TOVAR MANCERA, RAUL (HOSPITAL GENERAL, CD. MEXICO, DF, MEX, 1960)
1. Due to the fact that the use of a 0.4 per cent solution of sodium citrate in the opsonic test for the diagnosis of Brucella infection fails to prevent the action of "normal" opsonins, we found it advisable to increase to 1 per cent the final concentrat
J IMMUNOL
Keywords: OPSONIZATION, TEST, BRUCELLOSIS; CIENCIAS MEDICAS; PATOLOGIA; BACTERIOLOGIA MEDICA